2020
DOI: 10.1159/000510072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Near-Infrared Spectroscopy Devices for Assessing Tissue Oxygenation with a Vascular Occlusion Test in Healthy Volunteers

Abstract: Near-infrared spectroscopy devices can measure peripheral tissue oxygen saturation (StO 2). This study aims to compare StO 2 using INVOS ® and different O3™ settings (O3 25:75 and O3 30:70). Twenty adults were recruited. INVOS ® and O3™ probes were placed simultaneously on 1 side of forearm. After baseline measurement, the vascular occlusion test was initiated. The baseline value, rate of deoxygenation and reoxygenation, minimum and peak StO 2 , and time from cuff release to peak value were measured. The param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…This seems to be reflected in the slightly higher cut-off value in the INVOS dataset for detecting significant changes in SvO 2 . A previous study comparing these two devices also reported characteristics that aligns with the current finding 16 . The study compared the two devices with vascular occlusion tests in healthy volunteers.…”
Section: Discussionsupporting
confidence: 90%
“…This seems to be reflected in the slightly higher cut-off value in the INVOS dataset for detecting significant changes in SvO 2 . A previous study comparing these two devices also reported characteristics that aligns with the current finding 16 . The study compared the two devices with vascular occlusion tests in healthy volunteers.…”
Section: Discussionsupporting
confidence: 90%
“…[36][37][38] Yet, an intact superficial palmary arch is also crucial before the less commonly performed ulnar forearm free flap is harvested. 41,42 Another established approach to assess the microcirculation of the hand is to use a cuff occlusion test (COT) at the upper arm, which has been widely used as a comparative test for microcirculation monitoring before [43][44][45] and has already been reported in combination with HSI on a few patients. 16,24,[46][47][48] The purpose of this study was to both, qualitatively and quantitatively assess microcirculation of the hand in healthy volunteers during both a MAT and a COT at the upper arm using HSI.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, an intact superficial palmary arch is also crucial before the less commonly performed ulnar forearm free flap is harvested 41,42 . Another established approach to assess the microcirculation of the hand is to use a cuff occlusion test (COT) at the upper arm, which has been widely used as a comparative test for microcirculation monitoring before 43–45 and has already been reported in combination with HSI on a few patients 16,24,46–48 …”
Section: Introductionmentioning
confidence: 99%
“…Second, there were three NIRS instruments used for ScO 2 monitoring in the institutions, and all of the data were combined on the basis of an assumption and calibration of a certain arterial to venous volume ratio in the brain adopted in each device. However, the devices use different technologies and methods to provide cerebral oxygenation data, and several studies have shown positive correlations but disagreements between devices [33,34]. Some studies also suggested that evidence generated with one NIRS device may not be applied to other manufactures' devices [16].…”
Section: Discussionmentioning
confidence: 99%